GE_GERICHTE P/16965/2017 vom 8. April 2021 - GE Cour de justice (2021)
DESSEIN D'ENRICHISSEMENT;VOL(DROIT PÉNAL);INFRACTIONS CONTRE LE PATRIMOINE;FAUX MATÉRIEL DANS LES TITRES;BLANCHIMENT D'ARGENT | CP.139.ch1; CP.147.al1; CP.158.al1.ch1; CP.147.al1; CP.158.ch2; CP.251.ch1; CP.3.letc5bis.ch1